Increasing knowledge and attitudes about dental caries and prevention after educational intervention using a modified lecture method in adolescents - az zahra, Fatharani salsabila; Suryanti, Netty; Putri, Fidya Meditia (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: The prevalence of caries in adolescents is still high, and the average visit to the dentist is when the disease is advanced. Educational interventions about dental caries and prevention need to be carried out to improve oral health status. Providing oral health education with appropriate methods will increase knowledge and encourage changes in attitudes and behaviors to prevent adolescent dental caries. This study aimed to analyze the differences in knowledge and attitudes before and after the intervention of education on dental caries and prevention among adolescents using a modified lecture method. Method: The study design is Quasi-Experimental with one group pretest posttest research design. Sample selection used probability sampling techniques, with simple random sampling techniques. The population in this study was students of SMPN 1 Jatinangor, with the total sample of 186 respondents. Respondents were given educational intervention using a modified lecture method, namely giving a lecture, with the help of a powerpoint presentation with interesting pictures, providing a toothbrush demonstration and ending with a discussion group. Pretest and posttest assessment was using questionnaires. Pretest and posttest assessments used a questionnaire, which contained 20 knowledge questions and 15 attitude questions. Questionnaires and educational materials had been tested for validity and reliability, with Cronbach's alpha results for knowledge at 0,878 and attitude at 0,841. The data were analyzed with the Wilcoxon test. Results: There was a significant difference between knowledge before and after the intervention of education on dental caries and prevention with a p-value of 0.001 (<0.05), and there was an increase in knowledge score, there was an average increase in knowledge score of 52%. Likewise, there were differences in attitudes before and after the intervention, with a p-value of 0.001 (<0.05) and an increase in attitude scores of 7.95%. Conclusion: The modified lecture method using power points, videos, demonstrations, group discussions and roll play on brushing teeth, which are carried out on adolescents, can increase knowledge and attitudes towards dental caries and preventionKeywordsIntervention, education, knowledge and attitude, dental caries, prevention